Reshaping the Image of Women Owned Businesses in Difficult Times With Entrepreneurship Skills as Mediator Between Motivation and Efficiency : An Empirical Study - Samineni, Sridevi; Sudha, V. (AMC Indian Journal of Entrepreneurship, 2021)
COVID-19 pandemic disrupted the health, financial systems, and human relations across the globe. Economic and social systems are forced to adopt new ways. India too has witnessed negative growth rate during the pandemic and has been experiencing far greater effect on the whole population. On the other hand, women-owned small businesses were negatively affected and the revenue of their businesses declined due to underlying reasons like subdued demand, disrupted supply chain systems, and lack of flow of funds. Exceptionally, there are few women-owned businesses that witnessed gains by reshaping their businesses with their bold and courageous steps. Inner traits like motivation skills are the combination of notable motivating factors considered in the study for women to enter into business. The other variable is entrepreneurship skill to become self-reliant through self-confidence, self-control, creativity, adaptability, innovation, and influence for entrepreneurial growth. The third and important variable is efficiency skill which is the combination of communication, commitment, team capabilities, collaboration, and high profitability promoting mobilization with efficient linking up with other economic, social, and political interventions. This success and increase in their revenue have been predominantly driven by some of the inherent traits in women which are entrepreneurial in nature like innovation, creativity, reinvention, and adapting to new things. The present paper was an understanding of how the mediating effect between the mediator was undertaken to measure and inspect the straight and ancillary trails affecting the variables. The goal was to describe the provisional and depending instruments by which variable motivation skill communicates its effect with mediator(s) entrepreneurship skills on to the other variable efficiency skill using process macro3.1v of SPSS-21. The results showed that there was significant correlation between the three variables and the total effect of women motivational skills on women efficiency skills was suggestively variant from zero. Thus, it was assumed that women are confident in decision-making, holding and reshaping the image in these difficult times with their combined motivation skills and entrepreneurship skills leading to efficiency of their businesses.